Pengelolaan dan Konservasi Vegetasi Tanaman Gumi Banten di Desa Besakih, Kecamatan Rendang, Karangasem - Sundra, I Ketut (Bumi Lestari; Vol 23 No 2 (2023), 2023)
Taman Gumi Banten is an area that is utilized as a habitat for plant growth. An important background that supports Taman Gumi Banten is the preservation of rare plants classified as ceremonial plants, usada, and puspa dewata. This research aims to manage and conserve vegetation in the Taman Gumi Banten Besakih, as an effort to preserve ceremonial plants, usada, and puspa dewata. This research was conducted in Taman Gumi Banten Besakih with an area of 2 hectares, conducted for 3 months (May-July 2021). Sampling method with plot method.  Primary data, both vegetation data and soil data were taken at the observation site, while secondary data were taken from the Karangasem BMKG office. Data analysis was carried out with vegetation analysis, namely the importance value index, diversity index and species distribution pattern, and vegetation rarity status based on PERMENLHK No. 20 of 2018. While soil data will be analyzed at the Soil Science Laboratory, Faculty of Agriculture, UNUD. The results concluded that the number of species found was 101 species, consisting of 2297 individuals, with low diversity and uniform distribution patterns. There are 2 species classified as rare, namely the kasna kasna ( Anaphalis javanica ) and gegirang tree ( Leontopodium alpinum ), soil conditions especially high levels of organic carbon and soil texture all sandy loam are very supportive of vegetation development, and the number of plants in Taman Gumi Banten has only been fulfilled 2297 individuals while the shortage of 2703 individuals (being pursued).